2018
DOI: 10.1177/0886260518760014
|View full text |Cite
|
Sign up to set email alerts
|

Maltreatment and Affective and Behavioral Problems in Emerging Adults With and Without Oppositional Defiant Disorder Symptoms: Mediation by Parent–Child Relationship Quality

Abstract: The current study examined the indirect effect of maternal and paternal emotional and physical maltreatment on affective and behavioral symptoms of oppositional defiant disorder (ODD) through parent-child relationship quality; gender and overall ODD symptoms were examined as moderators. Participants included 2,362 emerging adults who completed questionnaires about parental emotional and physical maltreatment, parent-child relationship quality, and affective and behavioral ODD symptoms. These characteristics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…These findings provided a further understanding for interpreting ODD symptoms from a family system perspective. Compared with previous studies that simply explored one level of interaction—the whole level of parent–child relationships (Li et al, 2018; McKinney et al, 2018)—the current study investigated three levels of interactions. These findings are in line with the three‐level model of ODD (Lin et al, 2013) and highlight the urgency to decrease family violence within the Chinese family, to decrease parental alienation and to improve children's Emotion Regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings provided a further understanding for interpreting ODD symptoms from a family system perspective. Compared with previous studies that simply explored one level of interaction—the whole level of parent–child relationships (Li et al, 2018; McKinney et al, 2018)—the current study investigated three levels of interactions. These findings are in line with the three‐level model of ODD (Lin et al, 2013) and highlight the urgency to decrease family violence within the Chinese family, to decrease parental alienation and to improve children's Emotion Regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we included family violence as an entire level factor in the family system, parental alienation as a dyadic level factor in the family system and child ER as an individual level factor in the family system. Expanding upon prior research (Li, Lin, Chi, et al, 2016; Li, Lin, Hou, et al, 2016; McKinney et al, 2018), the current study examined whether parental alienation plays a mediating role between family violence and ODD symptoms. Additionally, given the importance of ER for the development of ODD (Lin, Li, Heath, et al, 2016), it was hypothesized that different levels of child ER (Lability/Negativity and Emotion Regulation) would have different effects on the relation between family violence and ODD symptoms.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Less research has examined the effect of continued adult child maltreatment by parents during emerging adulthood. In one recent study, researchers reported increased rates of substance use associated with maternal and paternal emotional maltreatment independently (Rogers et al, 2018) as well as increased rates of antisocial symptoms associated with general parental maltreatment (McKinney, Stearns, & Szkody, 2018).…”
Section: Parental Psychopathologymentioning
confidence: 99%
“…Moreover, research has indicated that ODD is best understood as an interaction among contextual factors, such as parental psychopathology, family cohesion, and discipline (Goodman et al., ). For example, parental depressive and anxiety problems and child maltreatment by parents have been associated with greater ODD problems in emerging adults (McKinney, Stearns, & Szkody, ). Additionally, Trepat, Granero, and Ezpeleta () found that corporal punishment mediated the relationship between maternal anxiety/depression and child ODD in a sample of preschoolers.…”
Section: Odd Problems In Emerging Adulthood and Gendermentioning
confidence: 99%